Acclimatization and efficacy of different transport systems for reducing stress of hilsa (Tenualosa ilisha) seeds during transportation: Hilsa seed transportation - Chattopadhyay, D. N.; Ray, P. K.; Chakraborty, A.; Mandal, R. N. (Journal of the Inland Fisheries Society of India, 2023)
Acclimatization and efficacy of different transport systems for hilsa (Tenualosa ilisha) seeds were evaluated. Different criteria such as nets used for capture, durations, containers, stocking-densities, air and oxygen filled polyethylene bags, temperature, locations and salinity were tested. Wild fry caught with lift net showed higher (P<0.05) survival (68%) than those caught with been jal (18%) and pata jal (38%). Wild fry in FRP tanks showed higher (P<0.05) survival (67-80%) than those in plastic tubs (0-20%) and aluminium hundi (0-20%), when stocked @ 1no./12 L for 5 hours acclimatization. Fry stocked @ 1 no./L for 6 hours acclimatization in air and oxygen filled polyethylene bags died within 4.48 hours and 20.17 hours in air and oxygen filled bags at 31.8 °C in laboratory; whereas all fry died within 1.5 hours in both air and oxygen filled bags, at 37.2 °C and 37.4 °C in field. Water temperature at 32.57-33.3 °C caused low survival (6.7-13.3%) of wild fry in one hour transport. Wild fry (60-90 mm) transport in aluminium hundi for 40-45 minutes showed varied survival. Reared fry survival was 100% in oxygen and air-filled bags for 6 hours acclimatization at stocking density of 3 nos./8 L unlike wild fry where survival was nil. Reared fry, stocked @ 1 no./L, 3 nos./L, 5 nos./L, and 7 nos./L, were transported in oxygen filled polyethylene bags for one hour survived between 92.38-100%. Pond reared fingerlings, stocked @ 1 no./3 L in oxygen filled polyethylene bags, were transported with varied salinities; of which 5 ppt, 7 ppt and 9 ppt showed significantly (P<0.05) higher survival (100%) than 0.3 ppt (66.67%). Pond reared fingerlings at 7 ppt with 1 no./L stocking in oxygen filled polyethylene bags survived 100% at one hour transportation. The study gives a direction of hilsa seeds transportation required for its domestication in captivity.